The Effect of 5R Implementation on Prevention of Occupational Accidents at the Nutrition Installation of Arifin Achmad Hospital, Riau Province: The Effect of 5R Implementation on Prevention of Occupational Accidents at the Nutrition Installation of Arifin Achmad Hospital, Riau Province - Pradani, Syakila; Endang Purnawati Rahayu; Ahmad Satria Efendi (JURNAL KESMAS DAN GIZI (JKG), 2025)
The results of research at the nutrition installation at Arifin Ahmad Regional Hospital, Riau Province in 2021, the implementation of 5R (concise, neat, clean, well cared for and diligent) has not run optimally, especially in the implementation of Neat, because dangers are still found such as slippery floors and items not being placed in the right place. resulting in the risk of work accidents. This research aims to see the effect of implementing 5R on preventing work-related accidents in the Nutrition Installation of Arifin Ahmad Hospital, Riau Province. This type of research is quantitative analytical observational, with a cross sectional design. The sampling technique was total sampling with a sample of 58 people. The results of the univariate analysis showed that the dominant 5R implementation had not been implemented, namely Neat implementation (69%). Implementation factors that have a relationship to work-related accidents based on bivariate analysis are 5R implementation, level of education and 5R knowledge. The results of the multivariate factors that have a dominant influence on work-related accidents in nutritional installations are that the level of education has a 5-fold risk of experiencing work-related accidents and the implementation of 5R has a 4-fold risk of experiencing work-related accidents. For this reason, efforts are needed to ensure that 5R implementation can be better, by creating SOPs, outreach, supervision during program implementation, and regular evaluations. The hope is that it can increase productivity and prevent work-related accidents at the Arifin Achmad Hospital Nutrition Installation, Riau Province, slippery floors and inappropriate placement of items. This creates a risk of work accidents.